University Education for Physical Education Students at Pedagogical Faculties in the Czech Republic - New Findings about First Aid for Spinal Injury - Pysny, Ladislav; Pysna, Jana; Petru, Dominika; Gőrner, Karol (Asian Journal of Education and Training, 2017)
Teaching physical education and sports at pedagogical faculties in the Czech Republic is often associated with certain risks which could lead to acute sports injuries. The most serious of these is traumatic spinal injury that could, in the case of poorly executed first aid, lead to serious damage to the health of individuals, including further unsolvable permanent consequences. Therefore every teacher or trainer as well as every student of physical education and sports must gain the necessary expertise in this field. This paper summarizes new findings about premedical first aid executed when a traumatic spinal injury occurs. It focuses especially on the appropriate assessment of disabilities according to Frankel and the implementation of specific procedures which can solve the trauma in various situations, including the use of a system for extricating an injured victim with a spinal fixation.